Optimizing Infrastructure Management as an Effort to Improve Educational Quality at MTS. Mathalibul Huda Mlonggo - Kamal Izzuddin; Sukarman Sukarman; Mustaqim Mustaqim (Lembaga Yasin AlSys, 2026)
Infrastructure management is a critical component of educational quality improvement, particularly in madrasah settings where learning effectiveness depends on the availability, usability, and sustainability of educational facilities. This study aims to analyze the optimization of infrastructure management as an effort to improve educational quality at MTs. Mathalibul Huda Mlonggo. The research focuses on infrastructure planning and procurement, the utilization and maintenance of educational facilities, and the contribution of infrastructure management to improving the quality of madrasah education. A qualitative approach with a case study design was employed. Data were collected through observation, in-depth interviews, and documentation involving the head of the madrasah, the vice principal for infrastructure, teachers, educational staff, students, and the madrasah committee. Data were analyzed using the Miles, Huberman, and Saldaña model, consisting of data condensation, data display, and data verification. The findings show that infrastructure management optimization is implemented through needs-based facility planning and procurement, sustainable utilization and maintenance of educational facilities, and management practices oriented toward learning effectiveness. The implementation of infrastructure management contributes to improving the quality of the learning process, the comfort of the learning environment, student motivation, educational service quality, and public trust in the madrasah. This study concludes that systematic and participatory infrastructure management can serve as an effective strategy for sustainably improving the quality of madrasah education. The study contributes to educational management practice by emphasizing the strategic role of facility governance in strengthening institutional quality, learning effectiveness, and community confidence.